Liquidation of Public Joint Stock Companies: Between Company Law and Insolvency Law under the Amended Company Law No. (20) Of 2023 - Alhadidi, Ismaeel (Dirasat: Shari’a and Law Sciences, 2024)
Objectives: This study aims to explore the interaction between the Insolvency Law and the Companies Law in light of Law no. (20) of 2023 amending the latter, whose object is to establish harmony between the two legislations. In fact, the Insolvency Law has primacy over the Companies Law when their respective scopes overlap. Thus, we have to study the impact of this primacy and know its dimensions when it comes to liquidating the public joint stock company. Methods: The descriptive and analytical approach was employed. The scope of application of liquidatitoins provided in the Companies Law and in the Insolvency Law was clarified. Results: This study concluded that the harmony expected from this amendment could not reach its full extent. Indeed, depriving the civilian public agent of state cases from requesting the insolvency, and the Court from declaring the insolvency on its own, constitute an obstacle to reach the pursued harmony. Moreover, the general controller of companies should be prevented from requesting compulsory liquidation, when a company is unable to fulfill its obligations. Conclusions: The civilian public agent of state cases should have the ability of requesting the declaration of insolvency of a public joint stock company. In addition, the study recommends to exclude resorting to the compulsory liquidation when the company is unable to fulfill its obligations. Moreover, resorting to compulsory liquidation is prohibited if the company’s losses reach 75% of its subscribed capital while it is subject to one of the insolvency law procedures.